Globalisation and Linkages Macro-Structural Challenges and Opportunities - Richardson, Pete (OECD Economics Department Working Papers, 1997)
This paper was prepared in the OECD Economics Department as a contribution to the Organisation-wide study entitled, "Towards a New Global Age". It examines macro-structural economic developments in and between OECD and non-OECD economies, the economic linkages and a number of structural factors and policies which have influenced growth performance. It goes on to consider a number of alternative forward-looking macroeconomic scenarios to 2020 for the world economy based on different hypotheses about economic policies and other factors influencing factor productivity developments. A final section provides a model-based evaluation of the potential influence of some of the key factors underlying these scenarios, in particular the influence of demographic changes such as population ageing and alternative fiscal policies ...